1999
DOI: 10.1136/fn.80.1.f54
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of trophic feeding and gut motility

Abstract: Objectives-To determine the eVect of trophic feeding on gastric emptying and whole gut transit time in sick preterm infants. Methods-A randomised, controlled, prospective study of 70 infants weighing less than 1750 g at birth, who were receiving ventilatory support, was performed. Group TF (33 infants) received trophic feeding from day 3 (0.5 ml/h if birthweight less than 1 kg, 1 ml/h if greater or equal to 1 kg) in addition to parenteral nutrition until ventilatory support finished. Group C (37 infants) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 22 publications
1
40
0
6
Order By: Relevance
“…Although the ultimate etiology of NEC remains unknown, studies have shown that certain feeding practices may be associated with decreased NEC rates. Although trophic feedings, or the provision of small volume, nutritionally insufficient feeds, have not been statistically associated with decreased NEC rates in systematic reviews, 20,21 they have been shown to stimulate gastrointestinal development [22][23][24][25] and promote gut motility 26 in premature infants. Studies have also shown a benefit to the use of human milk as the primary nutritional substrate for premature infants, with significant decreases in NEC rate associated with increased use of breast milk, both mother's own and donor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ultimate etiology of NEC remains unknown, studies have shown that certain feeding practices may be associated with decreased NEC rates. Although trophic feedings, or the provision of small volume, nutritionally insufficient feeds, have not been statistically associated with decreased NEC rates in systematic reviews, 20,21 they have been shown to stimulate gastrointestinal development [22][23][24][25] and promote gut motility 26 in premature infants. Studies have also shown a benefit to the use of human milk as the primary nutritional substrate for premature infants, with significant decreases in NEC rate associated with increased use of breast milk, both mother's own and donor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early trophic feeds do not increase susceptibility to developing NEC. However, studies have not yet clearly delineated the best feeding strategies for premature infants [147] .…”
Section: Trophic Feedsmentioning
confidence: 99%
“…Trophic feeds improve the activity of digestive enzymes, enhance the release of digestive hormones and increase intestinal blood flow and digestive motility in premature infants [147] . In addition, infants given early trophic feeds seem to have better feeding tolerance, improved growth, reduced period of hospitalization and decreased likelihood of sepsis compared with infants who are not [147] . Furthermore, early trophic feeds do not increase susceptibility to developing NEC.…”
Section: Trophic Feedsmentioning
confidence: 99%
“…Among the advantages of minimal enteral nutrition are the promotion of intestinal motility, better food tolerance, decrease in the incidence of sepsis and induction of lactase activity. 65 These advantages have not been totally confirmed after systematic literature review. 66 Most preterm infants born at less than 34 weeks of gestation are fed through a nasogastric or orogastric tube due to their difficulty in synchronizing sucking, swallowing, and breathing.…”
Section: Lipid Requirements Of Preterm Infantsmentioning
confidence: 92%